Edukasi Pemanfaatan Obat Tradisional, Aromaterapi, dan Akupresur untuk Mengurangi Kelelahan pada Tenaga Kesehatan dan Pasien di Rumah Sakit Universitas Airlangga: Educational Intervention on the Use of Traditional Medicine, Aromatherapy, and Acupressure to Reduce Fatigue Among Healthcare Workers and Patients at Airlangga University Hospital - Handayani, Rosita; Sukardiman, Sukardiman; Widyowati, Rr. Retno; Imandiri, Ario; Ekasari, Wiwied; Sudjarwo, Sudjarwo; Hafid, Achmad Fuad; Wahyuni, Tutik Sri; Lestari, Maria Lucia Ardhani Dwi; Sulistyowaty, Melanny Ika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Excessive fatigue and burnout are serious issues frequently experienced by healthcare workers and patients with chronic illnesses, particularly within high-pressure healthcare environments. These conditions not only impair the performance of medical personnel but also negatively affect the therapeutic outcomes of patients. To address this problem, a community service activity was conducted through educational outreach on fatigue and burnout management, utilizing acupressure, traditional remedies, and aromatherapy. The program involved 49 participants, including healthcare workers and Surabaya's chronic disease patients. Held on September 11, 2024, the activity employed lectures and two-way discussions as its primary methods. The material covered included traditional medicine, basic acupressure techniques, and training in roll-on and massage oil aromatherapy preparation. A structured module was developed to enhance learning effectiveness, and participants' comprehension was evaluated through pre- and post-tests. Statistical analysis using a paired t-test revealed a significant improvement in participants' understanding (p <0.01), with an average score increase of 19.8%. This initiative demonstrates that practical and interactive education can effectively improve participants' knowledge and skills in managing fatigue and burnout. Therefore, the outcomes of this activity are essential as a promotive and preventive effort to support the physical and mental well-being of vulnerable groups in healthcare settings.